Indian Villages - Gilbert Etienne (Graduate Institute Publications, 2014)
This book presents a unique testimony on the evolution of the Indian peasant's world over more than sixty years. Its originality lies in part in the unique trajectory of its author, Gilbert Étienne, an exceptional man, all at once scientific traveller, thinker of the North/South relationships and economist concerned by sociology and history inputs. In unfolding the story of his passionate relationship with India, the author offers a very personal look which takes into account not only crop di...